How South African Rewards Programs Impact On Customer Loyalty - Foley, Kyli (The IIE, 2020)
This research is addressed to all organisations interested in offering their loyal consumers a rewards program that provides valuable incentives in return for an on-going mutually beneficial relationship. There is uncertainty as to whether rewards programs are effective in positively influencing customer purchasing decisions and ensuring loyalty to a brand. This is a problem for companies injecting large amounts of capital into these initiatives. This research therefore discusses how South African rewards programs impact on customer loyalty. This small-scale study explores the link between rewards programs and how customers perceive them in order to determine whether South African rewards programs and their incentives increase customer purchases, reinforce client retention and support loyalty to a brand. From this research companies will be able to decide how they can better their loyalty services. Additionally, customers will benefit as they will receive improved incentives tailored to their needs. This study is qualitative, utilising in-depth interviews in order to gain information from respondents. This method of data collection and thematic analysis enabled the research to learn more about consumer views, opinions and beliefs, providing a subjective experience from the consumers point of view. Findings of this study show that customers value meaningful rewards. Companies ought to be injecting the necessary resources into running loyalty programs and offering their customers unique and valuable incentives. These programs have the ability to generate more than just a monetary return if they are well executed and offer mutual benefits to the brand and customer. If properly utilised, rewards program can aid in building meaningful relationships.
Keywords: Brand; Brand building; Brand loyalty; Loyalty programmes; Reward programmes